KAJIAN ELONGASI PADA TANAMAN IN VITRO GAHARU (Aquilaria beccariana van Tiegh) - Fauzan, Yusuf Sigit Ahmad; Sandra, Edhi; Mulyono, Daru (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2015)
The population density of natural agarwood (Aquilaria beccariana) in Indonesia decreased to less than one tree per hectare. Efforts have been carried out on ex situ conservation of agarwood despite facing many obstacles. In vitro propagation is one alternative to speed up the recovery of natural agarwood populations. The purpose of this study was to obtain optimal elongation media for in vitro culture with addition of auxin and cytokinin, namely IBA, BAP and kinetin. The results showed that the best auxin-cytokinin combination was IBA 0.1 mg/L and BAP 0.05 mg/L. This combination increased the height and number of segments of A. beccariana with an average height of 1.64 cm and average number of sections of 6.40. It is suggested that this combination of IBA and BAP was the most effective compared to the other treatments. In addition, the combination of IBA 0 mg/L and BAP 0.03 mg/L gave rise to the best response to increase the number of shoots with an average of 1.91 shoots.Keywords: Aquilaria beccariana, shoot, elongation, auxin, cytokinin ABSTRAKKepadatan populasi gaharu (Aquilaria beccariana) alam di Indonesia kurang dari satu pohon per hektar. Upaya pelestarian gaharu ex situ telah banyak dilakukan tetapi masih banyak kendala. Perbanyakan gaharu in vitro merupakan salah satu cara alternatif untuk mempercepat pemulihan populasi gaharu alam. Tujuan penelitian ini adalah untuk memperoleh media elongasi yang optimal pada kultur in vitro gaharu dengan penambahan kombinasi zat pengatur tumbuh auksin dan sitokinin. Pada penelitian ini digunakan auksin IBA, serta sitokinin BAP dan Kinetin. Hasil penelitian elongasi diperoleh kombinasi auksin dan sitokinin terbaik yaitu, IBA 0,1 mg/L dan BAP 0,05 mg/L. Kombinasi ini meningkatkan tinggi dan jumlah ruas Aquilaria beccariana dengan tinggi rata-rata sebesar 1,64 cm dan jumlah ruas rata-rata sebesar 6,40 ruas. Pada kombinasi dan taraf ini diduga mekanisme kerja IBA dan BAP paling efektif dibanding perlakuan yang lain. Sedangkan kombinasi IBA 0 mg/L dan BAP 0,03 mg/L memberikan respon terbaik terhadap peningkatan jumlah tunas dengan rata-rata sebanyak 1,91 tunas.Kata Kunci: Aquilaria beccariana, tunas, elongasi, auksin, sitokinin